2020
DOI: 10.3390/ijms21062165
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of Lumbar Intervertebral Discs: Characterization of Anulus Fibrosus Tissue and Cells of Different Degeneration Grades

Abstract: Intervertebral disc (IVD) herniation and degeneration is a major source of back pain. In order to regenerate a herniated and degenerated disc, closure of the anulus fibrosus (AF) is of crucial importance. For molecular characterization of AF, genome-wide Affymetrix HG-U133plus2.0 microarrays of native AF and cultured cells were investigated. To evaluate if cells derived from degenerated AF are able to initiate gene expression of a regenerative pattern of extracellular matrix (ECM) molecules, cultivated cells w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Intervertebral disc degeneration (IDD) is recognized as the major cause of LBP ( Smolders et al, 2013 ). Current treatment of IDD, including conservative therapies and surgical interventions, often only alleviates the patients’ pain without preventing the progression of IDD ( Stich et al, 2020 ). Furthermore, the clinical results are suboptimal ( Wang H. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intervertebral disc degeneration (IDD) is recognized as the major cause of LBP ( Smolders et al, 2013 ). Current treatment of IDD, including conservative therapies and surgical interventions, often only alleviates the patients’ pain without preventing the progression of IDD ( Stich et al, 2020 ). Furthermore, the clinical results are suboptimal ( Wang H. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al also demonstrated that an osteogenic medium could induce osteogenic transformation of rabbit AF cells by increased mineralization and expressions of Runx2, BMP-2, and osteopontin genes [ 18 ]. On the other hand, Stich et al used genome-wide microarray to evaluate the differences between human lumbar AF tissues from mild and severe degenerated IVDs and the results exhibited that Runx2 and other osteogenic-related genes were highly expressed in native AF tissues of severe degenerated IVD [ 48 ]. Similarly, Yeh et al confirmed that human AF cells of degenerated IVDs exhibited a higher tendency to osteogenic differentiation over native AF cells by an increase in the expression of mRNAs for BMP-2, Runx2, ALP, and osteocalcin and calcium deposition over native AF cells [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the selection of appropriate therapeutic genes, while important, is difficult and requires extensive knowledge of the pathogenesis of degradation, specifically timing and stage of degeneration. Besides, the AF cell apoptosis in degenerated IVDs is a barrier to the successful execution of gene-based therapies [ 95 , 96 , 97 ].…”
Section: Regenerative Strategiesmentioning
confidence: 99%
“…The effect of growth differentiation factors (GDFs) to enhance the anabolism-catabolism ratio in the ECM has been considered as an effective biomolecule-based regenerative strategy [ 93 , 97 ]. An increasing body of evidence indicated that GDFs were central to the IVD homeostatic processes, upregulation of the healthy cell marker genes in degenerative cells, and differentiation of mesenchymal stem cells to the NP cells [ 98 , 99 , 100 ].…”
Section: Regenerative Strategiesmentioning
confidence: 99%